Área da superfície e volume de prismas e cilindros - Geni Viana do Carmo Vendrame (2014)
The present study aims to investigate and analyze optimization problems related to the surface area and volume of prisms and cylinders. Intend to develop differentiated activities in search of alternatives to find the maximum volume of a solid with minimum area. This work allows students to broaden their knowledge and provides elements so that they can become independent in order to interpret, represent, to save and solve geometric problems. The use of manipulatives and computer technology in the teaching of geometry is a motivating and meaningful approach to learning. Thus, as with the knowledge of geometry throughout history, such studies in the drive to go in search of various ways to improve the knowledge of students and teachers, since they seek new methodologies that lead to transformation of the environment we live without neglecting methodologies above